DEVELOPMENT OF A MODEL OF PROFESSIONAL ACTIVITY THE ENGINEER AS DESIRED IMAGE OF THE FUTURE - Olga A. Linenko (Вестник Северо-Кавказского федерального университета, 2022)
In the framework of the performed research was carried out design model professional activity of an engineer. The basic characteristics of the educational preparation of future engineer.